Tribology of abrasive machining processes - Marinescu, Ioan D. (William Andrew Pub., 2004)
Recent and radically improved machining processes, from high wheel speeds to nanotechnology, have turned a spotlight on abrasive machining processes as a fertile area for further advancements. Written for researchers, students, engineers and technicians in manufacturing, this book presents a fundamental rethinking of important tribological elements of abrasive machining processes and their effects on process efficiency and product quality. Newer processes such as chemical mechanical polishing (CMP) and silicon wafer dicing can be better understood as tribological processes. Understanding the tribological principles of abrasive processes is crucial to discovering improvements in accuracy, production rate, and surface quality of products spanning all industries, from machine parts to ball bearings to contact lens to semiconductors.